Labour Costs and External Competitiveness of the Andalusian Economy (2007-2014). - Cardenete, Manuel Alejandro; Delgado, M. Carmen; Molero-Simarro, Ricardo (Revista de Estudios Andaluces, 2017)
The aim of this paper is to analyse the evolution of Andalusian economy’s external competitiveness. For that purpose, two main research dimensions are examined: first, the relationship between unit labour costs and Andalusia’s export performance at an aggregate level; second, indicators of both business, and public sector behaviour in the determinant areas of the regional competitive position at a microeconomic level. The analysis of the evolution of the variables in the economy will be carried out in comparison with several surrounding economies and regions. The results suggest that despite the strong downward trend followed by labour costs, at the moment, the crisis has not become an opportunity to substantially improve the positioning of the regional economy.